Generation UWB signal at energization of a helical antenna high-current REB - Balakirev, V.A.; Gorban’, A.M.; Egorov, A.M.; Kantemirov, A.V.; Lonin, Yu.F.; Ponomarev, A.G.; Onishenko, N.I.; Uvarov, V.T.; Chumakov, V.I.; Shevtusev, D.A.; Sherney, V.V. (Вопросы атомной науки и техники, 2006)
In operation the possibility of generation of UWB signal was researched at excitement of a helical antenna by a
high-current relativistic bundle of nanosecond duration. The experiments were conducted on a high-current relativistic
accelerator REB "Темр-А" with parameters: Eb ~ 0,5…1,0 МeV, Ib ~ 5…10 кА, duration of a ~15 nс., at the value
of a leading edge ~ 1…2 nс. The calculation data of a helical antenna and parameters of a generated UWB signal
are reduced. Исследовалась возможность генерации СШП-сигнала при возбуждении изолированной спиральной антенны сильноточным релятивистским пучком наносекундной длительности. Эксперименты проводились на сильноточном релятивистском ускорителе РЭП «Темп-А» с параметрами: Eb~ 0,5…1,0 МэВ, Ib~ 5…10 кА, длительность пучка ~15 нс, при величине переднего фронта ~ 1…2 нс. Приведены расчетные данные спиральной антенны и параметры генерируемого СШП-сигнала. Досліджувалася можливість генерації НШС-сигналу при збудженні спіральної антени
потужнострумовим релятивістським пучком наносекундной тривалості. Експерименти проводилися на
потужнострумовому релятивістському прискорювачі РЕП «Темп-А» з параметрами: Eb~ 0,5…1,0 МеВ, Ib~
5…10 кА, тривалість пучка ~15 нс, при величині переднього фронту ~ 1…2 нс. Приведено розрахункові дані
спіральної антени і параметри генеруємого НШС-сигналу